Prediction of rupture analysis and hemodynamic factors on abdominal aortic aneurysm for normal and high blood pressure subjects / Muhammad Rusydan Amir Hamzah - Muhammad Rusydan , Amir Hamzah (2012)
Abdominal aortic aneurysm (AAA) is a bulging and widening of the blood vessel due the weakening of aortic wall which may lead to rupture of aneurysm if it is not treated. Normally, the treatment of AAA is considered if the maximal diameter exceeds around 5-6cm. The increasing of the bulge is proportional to potential of aneurysm rupture. The ultimate goal of the study is to investigate the hemodynamic factors at the AAA region in terms of velocity, pressure and wall shear stress for normal and high blood pressure both at resting and exercise condition. The aneurysm model used in this study has been reconstructed from computed tomography scan (CT-scan). In order to simulate the behaviour of the hemodynamic factors, Computational fluid dynamic (CFD) and finite element analysis (FEA) software is used. The criteria of the flow are Newtonian and pulsatile flow. These criteria are applied in this simulation for both normal and high blood pressure at exercise and resting condition. Based on the results, the pressure distribution of the aneurysm is influenced by flow behaviour where it was found that pressure inside the aneurysm is proportional to blood velocity. On the other hand, wall shear stress (WSS) shows increment of stress in the early stage and reached its peak at the late stage of the periodic time. The hemodynamic factors considerably influence the expansion of aneurysm for both high and normal blood pressure. However, in every case experimented, hypertensive blood pressure during exercise exhibited greater hemodynamic effect in the aneurysm region due to active blood flow.